Curial y Güelfa: Arabic Narrative Form and the Poetic Structure of the cantigas de amigo (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
This essay suggests that the structure and poetic elements of the anonymous medieval Catalan “novela”, Curial y Güelfa, exemplify a mingling of Arabic elements. Taking into account the feminine sensibility that is always present in the Mozarabic poetic tradition, the possibility is presented of analysing this work like a novel with a traditional oriental structure that at the same time represents the inverse corpus (transformation from poetry to prose) of a long woman’s song or cantiga de amigo